Strategi Konten Visual dalam Pemasaran Digital: Studi Kasus Akun Instagram Sorai Merchandise - Putriajni, Anyelir Salsabila; Suhendi, Suhendi; Saputra, Nugroho Dwi (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
Instagram has become a primary platform in visual-based digital marketing strategies. This study aims to analyze the influence of visual design content on the effectiveness of digital marketing on Sorai Official Merchandise's Instagram account. A quantitative method was applied by distributing questionnaires to 129 followers of the account. The data were analyzed through validity and reliability tests, simple linear regression, and partial t-test. The results show that visual design content significantly affects digital marketing effectiveness, with a coefficient of determination (R²) of 55.6% and a significance value of < 0.001, which is under 0.05. Visual elements such as color, typography, illustration, and composition shape audience perception, encourage interaction, and influence purchase decisions. This research highlights the importance of a consistent and appealing visual content strategy to enhance the effectiveness of social media marketing.